Blood Transfusion and Its Effects - A.M. Sherene Christina Roshini1 , L.Malathi2 , E.Rajesh4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Sometimes blood transfusion causes adverse reactions. Better prognosisis obtained by understanding theclinical features of acute and delayed transfusion reactions.Current clinical practise involves better andnewer blood screening methods to reduce the complications. Selecting leukoreduction of red blood cells(RBCs) and male donors for plasma and restriction of RBC storage avoids infectious complications.